Health, health behaviors, and medical care utilization among college students with obesity - Hayes, Jacqueline F.; LaRose, Jessica Gokee; Hutchinson, Katherine; Sutherland, Melissa A.; Wing, Rena R. (Journal of American college health, 2025)
Objective: The study assessed perceived health, health behaviors and conditions, and medical care utilization among students of different weight categories. Participants: Participants were college students (n = 37,583) from 58 institutions who responded to a national survey of student health behaviors. Methods: Chi-squared and mixed model analyses were completed. Results: Compared to healthy weight students, those with obesity were less likely to report excellent health and meet dietary and physical activity recommendations, and more likely to have obesity-related chronic conditions and to have attended a medical appointment in the prior 12 months. Students with obesity (84%) and overweight (70%) were more likely to be attempting weight loss compared to students of healthy weight (35%). Conclusions: Students with obesity have poorer health and health behaviors relative to students of healthy weight; students with overweight were in between. Adapting and implementing evidence-based weight management programs within colleges/universities may be beneficial for student health.